If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + 2i)(1 + -4i) = 0 Multiply (7 + 2i) * (1 + -4i) (7(1 + -4i) + 2i * (1 + -4i)) = 0 ((1 * 7 + -4i * 7) + 2i * (1 + -4i)) = 0 ((7 + -28i) + 2i * (1 + -4i)) = 0 (7 + -28i + (1 * 2i + -4i * 2i)) = 0 (7 + -28i + (2i + -8i2)) = 0 Combine like terms: -28i + 2i = -26i (7 + -26i + -8i2) = 0 Solving 7 + -26i + -8i2 = 0 Solving for variable 'i'. Factor a trinomial. (1 + -4i)(7 + 2i) = 0Subproblem 1
Set the factor '(1 + -4i)' equal to zero and attempt to solve: Simplifying 1 + -4i = 0 Solving 1 + -4i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4i = 0 + -1 -4i = 0 + -1 Combine like terms: 0 + -1 = -1 -4i = -1 Divide each side by '-4'. i = 0.25 Simplifying i = 0.25Subproblem 2
Set the factor '(7 + 2i)' equal to zero and attempt to solve: Simplifying 7 + 2i = 0 Solving 7 + 2i = 0 Move all terms containing i to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2i = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2i = 0 + -7 2i = 0 + -7 Combine like terms: 0 + -7 = -7 2i = -7 Divide each side by '2'. i = -3.5 Simplifying i = -3.5Solution
i = {0.25, -3.5}
| 280=-6v+8(6v-7) | | 6b^2x^2-3bx=0 | | 2(3x+5)-4=-3x-30 | | 4x+r=b | | -2(x+3)+5x-6=6-(x-3)+2x | | 2*y=9-3*y-4 | | 689=p-41 | | 27=n+y | | 3w+7(w+8)=36 | | 4(2x-2)+10=-38 | | 9(2+2y)= | | 3-3*3+2= | | -6=5(y-6)+7y | | 3(4x-2)=-4x+26 | | x+3yi=6i | | 3w-15=2w-10 | | 2u+6(u+5)=14 | | 9w-31=6w-18 | | 3w-15=2w+10 | | 2(5x+1)-7=4x+7 | | 32x=-967 | | -11+6=-11 | | x^2+14x-23=0 | | 35x^5-2x=0 | | 144+8=78 | | (17-3)=5(17)+5(-3) | | -4x=35.3 | | y=4x+34 | | 13.7x=-523 | | 132=.15x | | 10-z=-8 | | 8.31x+58.17=116.34 |